Interlanguage Patterns in Written Arabic of Non-Native Speakers: Error Analysis Approach / أنماط اللغة البينية في الكتابة العربية للناطقين بغيرها: مدخل تحليل الأخطاء - Zuyyina Khuroisy; Hiraishin Mamoto (IJAS: International Journal of Arabic Studies, 2025)
This study investigates the linguistic patterns found in the written Arabic of non-native speakers through the lens of interlanguage theory and error analysis. The research aims to identify recurring grammatical, morphological, and syntactic errors that reflect transitional stages in second language acquisition. A qualitative approach was adopted, focusing on student-written texts from learners at the intermediate and advanced levels. The findings reveal systematic deviations from standard Arabic usage, such as subject–verb disagreement, misuse of prepositions, and incorrect application of verb patterns, all of which point to the presence of a developing internalized language system. These interlanguage patterns are shaped by the learners’ native languages, transfer strategies, and incomplete mastery of Arabic grammatical structures. The study underscores the need for pedagogical interventions that integrate contextualized grammar instruction and targeted writing feedback. It also highlights the significance of understanding interlanguage as a dynamic, rule-governed system rather than a set of random errors. Ultimately, the research contributes to the broader discourse on second language acquisition and offers implications for improving the teaching of Arabic as a foreign language.